PEMIKIRAN OTORITAS MAX WEBER DALAM PENGAMBILAN KEPUTUSAN DI SEKOLAH: STUDI KASUS DI PONDOK PESANTREN TARBIYAH ISLAMIYAH GOBAH V SURAU - Hadi Latif; Silfia Hanani (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine the implications of the application of Max Weber's authority thinking in the decision-making process at Pondok Pesantren Tarbiyah Islamiyah Gobah V Surau. This research uses a qualitative approach with a case study method to explore the application of Max Weber's authority thinking in decision making at the Tarbiyah Islamiyah Gobah V Surau Islamic Boarding School. The main focus of this research is to understand how Weber's three types of authority, namely traditional, charismatic, and rational-legal authority, play a role in the decision-making process involving pesantren leaders, teachers, and santri. The results of this study indicate that the application of Weberian authority in Pondok Pesantren Tarbiyah Islamiyah Gobah V Surau shows that the combination of traditional, charismatic, and rational-legal authority creates a strong and adaptive educational environment. Traditional authority safeguards spiritual and moral values, while the charismatic authority of leaders such as kyai builds loyalty among santri. On the other hand, the application of rational-legal authority increases efficiency and transparency in education management. Although there are challenges in maintaining traditional values in the midst of modernization, the combination of these three forms of authority provides a solid foundation for pesantren to adapt to the times, without losing its distinctive identity and character. Pondok Pesantren Tarbiyah Islamiyah Gobah V Surau has the potential to become a relevant and responsive educational institution, while being faithful to its existing cultural and spiritual heritage